Mapping the impacts of the anthropogenic activities and seawater intrusion on the shallow coastal aquifer of Port Said, Egypt - Abdelfattah, Mohamed; Abdel-Aziz Abu-Bakr, Heba; Aretouyap, Zakari; Sheta, Mariam Hassan; Hassan, Taher Mohammed; Geriesh, Mohamed H.; Shaheen, Shams El-Din; Alogayell, Haya M.; M. EL-Bana, Eman Mohamed; Gaber, Ahmed (Frontiers in Earth Science, 2023)
In Egypt, where the needs to meet the demands of the nation's projects and the expanding population are great, groundwater resources are now recognized as one of the major water sources. As a result of that, both the quantity and quality of these resources have been continually deteriorating, especially in coastal areas due to natural condition and anthropogenic activity. Thus, an integrated strategy using remote sensing, geophysical technique, and hydrogeochemical analysis is used in this work to identify the causes of degradation and evaluate their impacts on the groundwater quality in East Port Said, Egypt. Remote sensing analysis between 1984 and 2015 showed an increase in anthropogenic activities, such as the construction of fish farms and vegetation, which became their areas of 12.5 km2 and 37.8 km2 respectively. Due to their unplanned use of groundwater, it is expected that these human activities could have an impact on the groundwater quality. Therefore, a total of nineteen groundwater samples were collected from the shallow aquifer. For all groundwater samples, the major cations (Na+, Ca2+, Mg2+, and K+) and anions (HCO3-, SO42-, and Cl-) were analyzed for determining the hydrochemical composition. The hydrogeochemical graphs and plots show that the groundwater across the research area is of the Na-Cl water type and is highly saline (from 7558 to 23218 mg/L). The groundwater salinity was also identified by interpreting the geophysical resistivity method. This is clear evidence that that seawater intrusion is the main cause of groundwater salinity, and this intrusion can be accelerated by excessive pumping that drops the water table. These results serve as a solid base for further research on groundwater-surface water interactions and the evaluation of possible sources of contamination in the shallow aquifers under stress from anthropogenic activity in such environments.